Neutrophil extracellular traps and microglia/macrophages interactions in stroke: from thromboinflammation to immunotherapy - Ardic, Nurittin; Dinc, Rasit (Frontiers in Immunology, 2026)
Stroke remains a leading cause of death and disability worldwide, and inflammation is increasingly recognized as a key driver of acute injury and secondary neurodegeneration. Among post-stroke immune mediators, neutrophil extracellular traps (NETs) have emerged as critical amplifiers of thromboinflammation and cerebrovascular injury. Parallel developments highlight microglia and infiltrating macrophages as key regulators of sterile inflammation in ischemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH). However, the bidirectional interaction between NETs and microglia/macrophages has not been comprehensively analyzed despite its translational importance. This review describes the mechanistic pathways by which NET components activate microglial pattern recognition receptors, triggering inflammasome activation, inflammatory signaling cascades, and cytokine release. Activated microglia, in turn, promote neutrophil recruitment and NETosis, creating a self-reinforcing cycle. Evidence from ischemic and hemorrhagic stroke demonstrates how NET-microglia interactions lead to neurovascular complications such as blood-brain barrier disruption, microvascular dysfunction, and neuronal injury. We examine therapeutic strategies targeting NET formation and destruction, microglial modulation, and combination approaches to interrupt this inflammatory axis. We highlight novel biomarker and imaging approaches that may enable personalized immunotherapy. Together, these strategies position the NET-microglia/macrophage axis as a promising immunomodulatory target in ischemic and hemorrhagic stroke, offering new avenues for precision therapy development.